p53 activates circASCC3 to repress R-loops and enhance resistance to chemotherapy - Mingming Cao; Yu Gan; Yingdan Huang; Jing Tong; Chen Xiong; Yajie Chen; Bing Chen; Ruixuan Huang; Bangxiang Xie; Jun Deng; Shenglin Huang; Xianghuo He; et al. (Proceedings of the National Academy of Sciences, 2025)
The tumor suppressor p53 can trigger tumor resistance to chemotherapy by facilitating DNA damage repair and maintaining genomic integrity. Here, we report that a p53-induced circular RNA circASCC3 promotes chemotherapeutic resistance by resolving R-loops. Our results reveal that p53 directly activates the transcription of ASCC3 , the host gene of circASCC3. In addition, the RNA-binding protein SFPQ is identified to inhibit the formation of circASCC3 by associating with its flanking regions. Importantly, p53 facilitates the formation of circASCC3 by repressing the expression of SFPQ. CircASCC3 has a marginal effect on the survival and growth of cancer cells under normal growing conditions but surprisingly boosts their survival and growth in response to DNA damage stress. Mechanistic analysis reveals that circASCC3 binds to the DEAD-box RNA helicase DDX5 to inhibit its proteasomal degradation. This results in the prevention of R-loop accumulation due to DNA damage, thereby conferring tumor resistance to chemotherapy. Together, our study uncovers that p53 activates circASCC3 to promote R-loop resolution, which maintains genomic stability and potentially contributes to chemoresistance.